PENGARUH MODEL PEMBELAJARAN CHALLENGE BASED LEARNING (CBL) BERBASIS LABORATORIUM KEHIDUPAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN GEOGRAFI - Rifa Fitriyah F; Rery Novio (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to (1) Determine how the application of the Challenge Based Learning learning model based on life laboratories affects students' critical thinking skills in geography learning; (2) determine the effect of the Challenge Based Learning learning model based on life laboratories on students' critical thinking skills in geography learning. The research method used is the Quasi Experiment research method. The sample in this study consisted of E3 (control class) and X E5 (experimental class) which used the Challenge Based Learning model. Data were obtained from tests and a questionnaire. The results of the study showed that: (1) The application of the Challenge Based Learning (CBL) learning model based on life laboratories on students' critical thinking skills in geography learning had a positive effect on students' critical thinking skills, (2) The effect of the Challenge Based Learning learning model based on life laboratories on students' critical thinking skills in geography learning. This finding is shown in the increase in the average student score from the pretest result of 61.57 to the posttest average of 84.00. From the results of the average N-gain of the experimental class of 0.60 (quite effective category) it can be concluded that H0 is rejected and Ha is accepted because there is a difference in Geography learning outcomes between students who use the Challenge Based Learning model and students who use the conventional model at SMAN 1 V Koto Kampung Dalam. It can be concluded that the Challenge Based Learning model has a significant influence on geography learning.